TEMPORAL HORIZONS OF INFORMATION: RETENTION, PROTENTION, AND THE FLOW OF INFORMATIONAL MEANING - Dina M. Hammouri (Journal of Daoist Studies, 2026)
Information, conventionally understood as a static entity defined by transmission and representational content, increasingly fails to account for the temporal dimension inherent in the constitution of informational meaning. This study examines how informational meaning emerges, persists, and anticipates through time by drawing on phenomenological concepts of retention and protention. Retention refers to the temporal lingering of past informational events within present awareness, while protention designates the forward-reaching anticipatory structure that orients the reception of new information. Together, these temporal horizons constitute the living present of informational experience. The study argues that a genuinely dynamic model of informational meaning must integrate these temporal dimensions, displacing static representationalism accounts. Through a conceptual and comparative philosophical methodology, a Temporal Horizon Model of Informational Meaning is proposed and evaluated. The findings have implications for philosophy of information, cognitive science, communication theory, and artificial intelligence. The model offers a framework for understanding information not as discrete units of transmitted data but as a continuous temporal process in which meaning is constituted through the interplay of past retention, present encounter, and future anticipation.